Taḥlīlu Al-Akhtā’i Al-Kalāmiyyah Ladā Muʿallimī Al-Lughah Al-ʿArabiyyah fī Al-Marḥalah Al-Ibtidā’iyyah wa Al-Mutāwasitah bi Madīnah Madiun Jāwā Asy-Syarqiyyah - Prima Sari, Alvia Putri; Arisandi, Yusuf (Pascasarjana Universitas Islam Negeri Mataram, 2024)
Abstract The teacher plays an important role in teaching the Arabic language, especially in Madiun, East Java, in helping elementary and middle school students master their language competencies, particularly in speaking skills. However, a phenomenon has emerged in the form of linguistic difficulties or speech errors committed by the teachers. This research aims to uncover the linguistic errors found among Arabic language teachers. Data were collected through videos and interviews, and analyzed using Corder’s model, which consists of five steps: data collection, error classification, explanation of error causes, identification of error sources, and error evaluation. The results of this study indicate that phonological errors, such as incorrect sound articulation, affect local pronunciation. In terms of grammar, there are distinctions related to gender (masculine or feminine). The mother tongue (interference), such as Javanese or Indonesian, also has a strong influence on pronunciation and sentence structure used by the teachers, which causes interference that leads to incomplete Arabic pronunciation and sentence structure. Keywords: Error analysist, speaking skill, Arabic teachers